Extent of relationship between vitamin D deficiency and urinary tract infections (Texas Journal of Medical Science, 2022)
The study aimed to evaluate the relationship of vitamin D deficiency with urinary tract infections. One hundred and eighteen urine samples were collected from patients suffering from urinary tract infections (UTI) (46 males and 72 females) with different ages (20 to 70 years). The samples were collected from different Kirkuk hospitals during the period from October 2021 to December 2021. Different bacterial species were characterized, E.coli was the most predominant bacteria included 51 (43.2%) ((19 (41.3%) in males and 32(44.4%) in females)), followed by Klebisella spp.29 (24.5%) ((11 (23.9%)in males and 18 (25%) in females)). While Pseudomonas aeruginosa was isolated from 14(11.8%) ((5 (10.8%)in males and 9(12.5%) in females)), and Proteus was recorded in 14 (11.8%) (6 (13%)in males and 8 (11.1%) in females)), Staphylococcus aureus 6 (5%) ((3 (6.5%) in males and in females 3 (4.1%)). Enterococcus bacteria was the lowest bacteria isolated from UTI patients 4 (3.3%) ((2 (4.3%) in males while in females was 2 (2.7%). The results also showed that people with urinary tract infections were mostly vitamin D deficient in both sexes, (37.80.4%) of patients lacked vitamin D compared to normal people 9(19.5 %) and 8(11.1%).